Enhanced isosteric heat of adsorption and gravimetric storage density of hydrogen in GNP incorporated Cu based core-shell metal-organic framework. (27th November 2020) - K, Archana; Pillai, Nisha G.; K V, Sai Srinivasan; Chauhan, Pawan K.; Sujith, Ravindran; Rhee, Kyong Yop; A, Asif
Abstract: The present work explores the hydrogen adsorption potential of graphene nanoplatelet incorporated core-shell metal-organic frameworks (MOFs). Core-shell MOFs [(HKUST-1@Cu-MOF-2 (HM) and Cu-MOF-2@HKUST-1 (MH)] and their graphene nanoplatelets (GNP) incorporated composites [GNP@HKUST-1@Cu-MOF-2 (GHM) and GNP@Cu-MOF-2@HKUST-1 (GMH)] were synthesized by solvothermal method. The core-shell formation and the structural effect of graphene nanoplatelts incorporation was established and studied using X-ray diffraction analysis, thermogravimetric analysis, scanning electron microscopy and X-ray photoelectron spectroscopy. The hydrogen adsorption studies were carried out at maximum pressure of 2 bar and temperature of 100 K using Sievert's apparatus. GHM exhibited the highest storage capacity of 2.3 wt% at 100 K and 2 bar. Significantly, contrary to MH, the average pore size in HM increased from 1.66 nm to 2.58 nm after the addition of graphene nanoplatelets, resulting in Type IV N2 sorption isotherm as found through BET studies. Additionally, the theoretical isosteric heat of adsorption was estimated using the Clausius Clayperon equation where GHM showed an exceptionally high isosteric heat of adsorption of 14.7 kJ/mol. Therefore these studies on newly developed core-shell MOF/GNP bring out the effect of GNP incorporation on the structure of the MOF, formation of the local active centres and carbon clusters, which are critical to hydrogen adsorption. Graphical abstract: Image 1 Highlights: Maximum hydrogen uptake recorded was 2.3 wt% for the GNP@HKUST-1@Cu-MOF-2 sample. Isosteric heat of adsorption was 14.7 kJ/mol for the GNP@HKUST-1@Cu-MOF-2 sample. Hydrogen spillover enhancement contributes to high heat of adsorption in GNP.